PUNISHMENT & REWARD, IKLIM ORGANISASI, DAN KOMPETENSI TERHADAP PRODUKTIVITAS KARYA ILMIAH DOSEN PERSAUDARAAN DOSEN REPUBLIK INDONESIA (PDRI) SUMATERA SELATAN - Aravik, Havis; Zamzam, Fakhry; Marnisah, Luis (Universitas Indo Global Mandiri Palembang, 2021)
This research aims to analyze Punishment & Reward, organizational climate and potential for the productivity of the scientific work of PDRI South Sumatra lecturers. The research method used is quantitative research with descriptive and verification confirmative survey methods, with a population of 234 PDRI members in the Whatsapp (WA) group and 132 taken after being verified in answering questionnaires and interviews, as well as data processing using the SPSS 23 tool. that punishment & rewards for lecturers can affect productivity with t count 6.215> t table 1.976, organizational climate affects productivity with t count 6.215> table 1.976, and compensation affects productivity with t count of 4.044> t table 1.976, and punishment & reward, Organizational climate, and competence together affect productivity with F count of 26.484> F table 3.0663, with the output solvent coefficient of R Square 70.9%. Thus, that reward & reward affects productivity, organizational climate affects productivity, and competence affects productivity, and together punishment & reward, organizational climate, and competence affect productivity.Key words: punishment & reward, organizational climate, Competence, and Productivity